Evaluation of Nursing Care Management for Diabetes Mellitus Patient with Total Hip Replacement - Towfieq, Narmein (Iraqi National Journal of Nursing Specialties, 2007)
Objective: The aim of the study to evaluate the nursing care management for diabetes mellitus patient with total hip replacement after fractured hip. Methodology: A field study carried out on patients with diabetes mellitus and have total hip replacement after fractured hip in orthopedic ward at the hospital of surgical specialization (malefemale)during January 2002 to January 2003.Physical and psychological nursing assessment immediately after the surgery was done for the both subjects (control and experimental) and then a scientific management with daily nursing care were provided to the experimental subject with daily nursing care to the patient condition by using a scientific and practical methods and leave the control subjects on the ward nurses. An evaluation was done to the experimental subjects physically and psychologically before departing to their families again. Results: The results of the evaluation showed that most of the patients have many prognoses in their condition with less complication. Recommendation: According to the results of this study, the researchers recommended that the importance of orthopedic nurses education all the scientific and practical methods for this type of patients which is most of them was aged and have diabetes mellitus